Creation of antimicrobial biopolymers by the use of recombinant DNA technology - Costa, André Manuel Abreu (2016)
[Excerpt] The spread of antimicrobials resistant microorganisms has triggered the search for new ways to treat infections. One of these ways is the creation of antimicrobial devices and surfaces that kill or prevent the spread of microorganisms. In the present work we explored the properties of different antimicrobial peptides (AMPs) for the creation of biopolymers with broad antimicrobial activity. Antimicrobial recombinant protein-based polymers (rPBPs) were designed by cloning the DNA sequence coding for the different AMPs in frame with the N-terminus of the elastin-like recombinamer consisting of 200 repetitions of the pentamer VPAVG, here named A200. [...]